The predicament of justice: fifty years of Armed Forces Special Powers Act in India - Kikon, Dolly (Contemporary South Asia, 2009)
Militarisation and structural violence under the Armed Forces Specials Powers Act (AFSPA) is tied to a strong moral framework to proselytise recalcitrant citizens. Deploying Jacque Derrida's point that law is not justice, this paper highlights how the pursuit of justice within the framework of law is a challenging task. Interrogating the contentions around what constitutes 'justice' under the AFSPA, this paper exposes how states legitimise lawlessness through draconian laws like the AFSPA. In this manner, lawlessness is established as a precedent for states to reproduce forms of lawless regimes and undemocratic mechanisms. This paper proposes that along with the campaigns to repeal the AFSPA, we need to reflect upon what kind of justice we seek. Repressive and discriminatory regimes of law, government or practice survive even after they have been formally dismantled. Here, both the state and its citizens negotiate reality regarding the limits of justice in their own way. For the Indian state, it has had to constantly over-extend its coercive powers in order to control the situation. While for its citizens who live under the AFSPA, such a reality is not only a matter of concern but it also redefines their position as citizens/subjects, to the extent that they question the very foundations of democracy, the language of rights and the unsatisfied appeal of justice. Their negotiations are a reminder that the state apparatus' exercise of power has largely remained unchanged in Northeast India. Despite the framing of rights - be they as part of colonial edicts or postcolonial constitutions - there are spaces where the limits of this discourse are constantly questioned.